WEIGHING IRAN’S NUCLEAR: CONSTRUING REALITY THROUGH ITS OPPOSITION - Habiba Al Umami (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Political speech has been an interesting social phenomenon to study. The languageinterplays within political discourse discover more than what is said. This studyanalyzes Benjamin Netanyahu speech in the United Nations General Assembly(UNGA) 2013 under the discussion of nuclear Iran. The study focuses on therepresentation of nuclear Iran based on Benjamin’s perspective and uncovers thepower strata between Iran and Israel. The study is conducted under a qualitativeapproach by using the three stages model of Critical Discourse Analysis andSystemic Functional grammar approach. The result of the study indicates thatnuclear Iran has the capability to contribute several impacts in the energy sector,peace and resolution process worldwide, and terrorism sphere in the Middle East.Benjamin’s speech also mirrors the power strata between Iran and Israel. Morespecifically, Benjamin implicitly acknowledges Iran as a powerful party within thediscourse.